AFIKS-AFIKS DERIVASI BAHASA INGGRIS DAN BAHASA BATAK TOBA (SUATU ANALISIS KONTRASTIF) - BANJARNAHOR, ARMIN SAWARI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â Â This research is entitled â€œAfiks-Afiks Derivasi Bahasa Inggris dan Bahasa Batak Toba (Suatu Analisis Kontrastif)â€, written as a research report to describe and analyze the derivational affixes of both English and Toba Batak language in term of form, function and meaning in verb, noun, adjective, and adverb. The objective of this research is to find out the similarities and the differences of derivational affixes in English and Toba Batak language by using Oâ€™Gradyâ€™s (1987) theory and contrasting them using Ladoâ€™s (1971) method.Â  The English data were collected from several English textbooks, namelyÂ  Contemporary Linguistic Analysis : An Introduction (1987) by Oâ€™Grady and the data of Toba Batak Language were taken from four native speakers as informants who were born and lived in the land of Toba Batak and they were selected based on age, gender, and intelligence.Â  The results of this research show that the types of English derivational affixes are prefixes and suffixes. The types of Toba Batak derivational affixes are prefixes, suffixes, infixes, and confixes. The functions of both English and Toba Batak derivational affixes are to create new lexeme that may change the parts of speech or not.Â  The similarities of English and Toba Batak derivational affixes are both English and Toba Batak derivational affixes have prefixes and suffixes process. The differences of both derivational affixes are English derivational affixes form new English words through prefixation and suffixation; meanwhile, there are infixation and confixation in Toba Batak language. In context of meaning, English derivational affixes have prefixes that have negative meaning, but Toba Batak derivational affixes have no prefixes that denote negative meaning. Â Key Word : Derivational Affixes of English, Toba Batak language, Contrastive Analysis.